Perkembangan Agama pada Usia Sekolah (6-18 Tahun) dalam Perspektif Islam - Miftahurrahmat, Miftahurrahmat; Jannah, Miftahul; Syauky, Ahmad (Indo-MathEdu Intellectuals Journal, 2025)
This study examines the stages of religious development in school-aged children (6-18 years) from an Islamic perspective, focusing on the role of education, environment, parents, and teachers. The main argument of the study states that each age phase has different spiritual characteristics: elementary school age (6-12 years) is concrete with the habit of worship, junior high school age (13-15 years) is marked by the search for religious identity through reflection on values, and high school age (16–18 years) leads to the internalization of values into religious attitudes. The study employs a qualitative approach using literature review methods, collecting data from primary sources (exegesis, hadith, developmental psychology) and secondary sources (journals, books, policy documents). Findings indicate that the emotional bond between children and their parents and teachers significantly influences the reinforcement of religious values, particularly in instilling moral values, worship, and role modeling. Evidence suggests that students' spiritual crises often stem from weak religious upbringing from an early age. This study recommends strengthening school-home collaboration, integrating spiritual values into a holistic curriculum, and age-specific approaches. In conclusion, children's religious development requires synergy between parental role modeling, teachers' contextual teaching methods, and a conducive environment. This study contributes to the development of an Islamic education model that balances cognitive, affective, and spiritual aspects.